2019
DOI: 10.7717/peerj.7557
|View full text |Cite
|
Sign up to set email alerts
|

HiLDA: a statistical approach to investigate differences in mutational signatures

Abstract: We propose a hierarchical latent Dirichlet allocation model (HiLDA) for characterizing somatic mutation data in cancer. The method allows us to infer mutational patterns and their relative frequencies in a set of tumor mutational catalogs and to compare the estimated frequencies between tumor sets. We apply our method to two datasets, one containing somatic mutations in colon cancer by the time of occurrence, before or after tumor initiation, and the second containing somatic mutations in esophageal cancer by … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…After classifying our mutations into time of occurrence, trunk or branch, we found the signature for aging (red) was more frequent in trunk than branch mutations from MSS tumors but the same was not true for MSI tumors. This replicates the results from an earlier study of MSS colon cancers that also found a higher mutational exposure of the aging signature in trunk compared to branch mutations [14]. The lack of any new mutational signature in branch mutations, despite the different micro-environments of cancer from normal colon, is interesting.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…After classifying our mutations into time of occurrence, trunk or branch, we found the signature for aging (red) was more frequent in trunk than branch mutations from MSS tumors but the same was not true for MSI tumors. This replicates the results from an earlier study of MSS colon cancers that also found a higher mutational exposure of the aging signature in trunk compared to branch mutations [14]. The lack of any new mutational signature in branch mutations, despite the different micro-environments of cancer from normal colon, is interesting.…”
Section: Discussionsupporting
confidence: 89%
“…Finally, we applied a hierarchical latent Dirichlet allocation model (HiLDA) [14] to test the equivalence of mutational signature exposures between trunk and branch mutations. We used the posterior distributions of the mean differences to test for differential exposures for any single signature (signature-level tests).…”
Section: Main Textmentioning
confidence: 99%
“…Such comparison tests are usually performed directly on the number of mutation counts or the estimated contributions. While such statistical methods presented a way to aid the process of discovering the associated mutagenic processes, a recent study by Yang et al argued that such comparison tests may struggle with low power and efficiency due to the tests ignoring the variance of the estimated contributions 14 . Especially, when the total number of observed mutations is low, which may result from low sequencing coverage, low tumor purity, and/or low mutational burden, the accuracy of the estimated contributions may vary across samples and across signatures.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous methods that allow for finding de novo signatures have been introduced. These methods detect mutational signatures based on various algorithms including Bayesian NMF 4 5 , other variations of NMF 6 7 9 10 11 , expectation-maximization 12 , or mixed-membership models 13 14 . These methods can detect novel signatures including ones that resemble the composition of mutational contexts in COSMIC signatures.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of important mutational processes with distinct mutational signatures include aging and ultraviolet (UV) radiation. Additionally, many research groups are performing analysis to discover de novo mutational signatures in cancer [1][2][3][4] .…”
Section: Introductionmentioning
confidence: 99%